Modular specification of frame properties in JML - Müller, Peter; Poetzsch-Heffter, Arnd; Leavens, Gary T. (Concurrency and computation, 2003)
We present a modular specification technique for frame properties. The technique uses modifies clauses and fields with declared dependencies. Modularity is guaranteed by a programming model that enforces data ion by preventing representation and argument exposure, a semantics of modifies clauses that uses a notion of ‘relevant location’, and by modularity rules for dependencies. For concreteness, we adapt this technique to the Java Modeling Language, JML. Copyright © 2003 John Wiley & Sons, Ltd.